Stereotactic body radiation therapy for metastasis to the adrenal glands. Issue 12 (December 2012) - Shiue, Kevin; Song, Andrew; Teh, Bin S; Ellis, Rodney J; Yao, Min; Mayr, Nina A; Huang, Zhibin; Sohn, Jason; Machtay, Mitchell; Lo, Simon S
Many primary cancers can metastasize to the adrenal glands. Adrenalectomy via an open or laparoscopic approach is the current definitive treatment, but not all patients are eligible or wish to undergo surgery. There are only limited studies on the use of conventional radiation therapy for palliation of symptoms from adrenal metastasis. However, the advent of stereotactic body radiation therapy (SBRT) – also named stereotactic ablative radiotherapy for primary lung cancer, metastases to the lung, and metastases to the liver – have prompted some investigators to consider the use of SBRT for metastases to the adrenal glands. This review focuses on the emerging data on SBRT of metastasis to the adrenal glands, while also providing a brief discussion of the overall management of adrenal metastasis.